2021
DOI: 10.5498/wjp.v11.i6.232
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 impact on high school student’s education and mental health: A cohort survey in China

Abstract: BACKGROUND The ongoing coronavirus disease 2019 (COVID-19) pandemic and the universal implementation of control measures are fundamentally affecting every aspect of our society and daily lives. AIM To evaluate the prevalence of post-traumatic stress disorder symptoms and their associated factors as well as the effects and attitudes towards online education in Chinese high school students. METHODS A total of 883 students were included. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The COVID‐19 pandemic provides a traumatic experience for high school teenagers (Z.‐R. Ma et al, 2021 ). Female adolescents are reported to have higher PTSD symptoms than males (Hu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The COVID‐19 pandemic provides a traumatic experience for high school teenagers (Z.‐R. Ma et al, 2021 ). Female adolescents are reported to have higher PTSD symptoms than males (Hu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Adolescents who live in rural areas have a higher risk of PTSD than adolescents in urban areas (Z.‐R. Ma et al, 2021 ). Lower parental education level is associated with lower PTSD risk (Z.‐R.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, preliminary evidence points toward the detrimental effects of COVID-19-related to quarantine on mental health as it has shown links to depression, stress, panic attacks, phobic symptoms, low mood and post-traumatic stress symptoms[ 9 ]. Considering that the symptoms of acute, as well as chronic stress [and in its most severe manifestation, posttraumatic stress disorder, (PTSD)[ 10 ]] have been associated with an array of destabilizing situations, such as war[ 11 ], financial crises[ 12 ] and natural disasters[ 13 ], and also with the psychopathology associated with trauma[ 14 , 15 ]. Exploring the effects of stress and its consequences during the COVID-19 outbreak seems important both theoretically and clinically.…”
Section: Introductionmentioning
confidence: 99%
“…These levels of psychological distress were higher than those reported in a meta-analysis of studies among the general population [ 5 ], suggesting that the pandemic had distinctive effects on the mental health of teachers. Studies on teachers from different countries have further highlighted their deteriorating mental health and well-being (e.g., Australia [ 3 ], Spain [ 2 ] and China [ 6 ]). For example, a longitudinal study [ 7 ] in the United Kingdom reported an increase in the levels of anxiety among teachers following school closures and transition to remote learning.…”
Section: Introductionmentioning
confidence: 99%